1997
DOI: 10.1016/s0550-3213(97)00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian embedding of the massive Yang-Mills theory and the generalized Stückelberg formalism

Abstract: Using the general notions of Batalin, Fradkin, Fradkina and Tyutin to convert second class systems into first class ones, we present a gauge invariant formulation of the massive Yang-Mills theory by embedding it in an extended phase space. The infinite set of correction terms necessary for obtaining the involutive constraints and Hamiltonian is explicitly computed and expressed in a closed form. It is also shown that the extra fields introduced in the correction terms are exactly identified with the auxiliary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…Finally, we would like to comment on the interesting work recently done by Banerjee and Barcelos-Neto [29]. After finishing our work, we have found that their work is similar to our work.…”
Section: B Lagrangian From the Hamilton's Equation Of Motionsupporting
confidence: 66%
“…Finally, we would like to comment on the interesting work recently done by Banerjee and Barcelos-Neto [29]. After finishing our work, we have found that their work is similar to our work.…”
Section: B Lagrangian From the Hamilton's Equation Of Motionsupporting
confidence: 66%
“…The method also permit us to obtain any involutive quantity that has zero Poisson brackets with all the constraints. The embedding Hamiltonian can be obtained in this way, starting from the initial canonical Hamiltonian and iteratively calculating the corresponding corrections.There is another manner to obtain an embedding Hamiltonian, which consists in using the BFFT method to obtain involutive coordinates [4]. The canonical Hamiltonian is then rewritten in terms of these new coordinates that automatically give it the involutive condition.…”
mentioning
confidence: 99%
“…The transformation of constraints from second to first-class is achieved after extending the phase space by means of auxiliary variables under the general rule that there is one pair of canonical variables for each second class constraint. The method is iterative and can stop in the first step [3] or can go on indefinitely [4,5]. In any case, after all constraints have been transformed into first-class, it is necessary to look for the Hamiltonian corresponding to this new theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in the usual BFT Hamiltonian embedding of the model we would have identified two auxiliary fields with a pair of conjugate fields as coordinate and momenta [6,7,[9][10][11].…”
mentioning
confidence: 99%